Dopplervelocimetria da artéria oftálmica em gestantes pré-eclâmpticas com recém-nascidos portadores de restrição de crescimento - Freitas, Marta Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Among hypertensive disorders that affect pregnancy, preeclampsia (PE) is the leading cause of mortality in short and long-term maternal morbidity and also perinatal complications such as premature birth, growth restriction and death. The examination of eye reflects changes arising from systemic vasospasm, a basic change in the disease pathophysiology. The Doppler of ophthalmic arteries is a reproducible and noninvasive, thus becoming an objective method that sets the manifestations of hypertension among themselves, enhances the understanding of the preeclampsia pathophysiology and identifies the severity of the disease, directly related to the central nervous system compromising. Objective: To identify if there is a relationship between changes in the Doppler of the ophthalmic artery of pregnant women with PE and the occurrence of fetal growth restriction. Subjects and Methods: Across sectional study in a population of 75 pregnant women with a diagnosis of PE, who had pregnancy resolution at Regional Hospital of Gama - Federal District and whose newborns were classified according to their weight for gestational age (SGA - small for gestational age and not SGA) according to Lubchenco table. The dopplervelocimetry of the ophthalmic artery was performed in 17 Nemio Toshiba equipment with linear transducer in the frequency of 10 MHz and, the following parameters were determined: resistance index (RI), pulsatility index (PI), systolic velocity peak(SVP), end-diastolic velocity (EDV) and velocity ratio peak (VRP). Statistical analyses were performed using ANOVA and Chi-square test. The results were considered statistically significant with p values <0.05. Results: Analysis of maternal clinical characteristics, according to the newborns classification (Not SGA and SGA), showed no significant difference in maternal age (27.7+6.8 years vs 29.5+7, 4 years), parity (48.2% vs 50%) and the rate of cesarean delivery (84.7% vs 100%). ...

Introdução: Dentre as síndromes hipertensivas que acometem a gestação, a pré-eclâmpsia (PE) é a principal causa de mortalidade e morbidade materna a curto e longo prazo, e de complicações perinatais como prematuridade, restrição do crescimento e óbito. O exame de fundo de olho reflete as alterações decorrentes do vasoespasmo sistêmico, alteração básica na fisiopatologia da doença. O Doppler das artérias oftálmicas é um exame reprodutível e não invasivo, constituindo-se em um método objetivo que diferencia as formas de manifestação da hipertensão entre si, aprimora a compreensão da fisiopatologia da pré-eclâmpsia e identifica a gravidade da doença, diretamente relacionada com o comprometimento do sistema nervoso central. Objetivo: Identificar se existe relação entre as alterações verificadas no Doppler da artéria oftálmica de gestantes portadoras de PE e a ocorrência de restrição de crescimento fetal. Sujeitos e métodos: Realizou-se estudo de corte transversal em uma população de 75 gestantes com diagnóstico de PE, que tiveram a resolução da gestação no Hospital Regional do Gama - Distrito Federal e cujos recém-nascidos foram classificados de acordo com a adequação do peso para a idade gestacional (PIG - pequeno para a idade gestacional e não PIG), segundo a tabela de Lubchenco. O exame dopplervelocimétrico da artéria oftálmica foi realizado em equipamento Toshiba Nemio 17, com transdutor linear na frequência de 10 MHz, determinando-se os seguintes parâmetros: índice de resistência (IR), índice de pulsatilidade (IP), pico de velocidade sistólica (PVS), velocidade diastólica final (VDF) e razão entre picos de velocidade (RPV). A análise estatística foi realizada utilizando os métodos ANOVA e Qui-quadrado. Os resultados foram considerados estatisticamente significativos quando apresentaram valores de p <0,05. Resultados: A análise das características clínicas maternas, segundo...
Keywords: Dopplervelocimetria; Pré-eclâmpsia; Hipertensão na gravidez; Arteria oftálmica; Ophthalmic Artery; Hypertension in pregnancy; Doppler ultrasonography